2016
DOI: 10.1002/jmv.24486
|View full text |Cite
|
Sign up to set email alerts
|

Genetic detection of hantaviruses in rodents, Albania

Abstract: In order to have a first insight into the epidemiology of hantaviruses in Albania, 263 small mammals (248 rodents, 15 insectivores) were captured in 352 locations in 29 districts and tested for hantavirus infection. Dobrava-Belgrade virus (DOBV) was detected in 10 of 148 (6.7%) Apodemus flavicollis rodents. DOBV-positive A. flavicollis were detected in six districts (Diber, Korce, Kolonje, Librazhd, Pogradec, and Vlore). The obtained nucleotide sequences were highly similar to each other and to DOBV sequences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Phylogenetic analysis revealed that two variants of DOBV circulate in Romania . In Albania, 263 small mammals were trapped during 2006‐2007; 10 of 148 A. flavicollis rodents were found to be infected with DOBV …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phylogenetic analysis revealed that two variants of DOBV circulate in Romania . In Albania, 263 small mammals were trapped during 2006‐2007; 10 of 148 A. flavicollis rodents were found to be infected with DOBV …”
Section: Discussionmentioning
confidence: 99%
“…Prevention is important due to the lack of effective antivirals . Surveillance offers important data on the infection in wildlife and hantavirus prevalence and thus facilitates prediction of possible outbreaks …”
Section: Introductionmentioning
confidence: 99%
“…Their prevalence in Western Palearctic and common status in Western and Central Europe made them one of the model organisms to study post-glacial movement of mammals [24, 45]. Both species have traditionally been studied in a parasitological context, as one of the vectors of Borellia -carrying ticks Ixodes ricinus , who often feed on Apodemus [13, 61], tick-borne encephalitis virus [47] and hantaviruses [33, 50] and have been used as markers for environmental quality [40, 66]. Lastly, they have extra-autosomal chromosomes, called B chromosomes, with varied distribution among the populations [59] but unknown role, although it has been suggested they are involved in cellular metabolism [34, 39].…”
Section: Introductionmentioning
confidence: 99%
“…In Albania, the major causative hantavirus agent is Dobrava-Belgrade virus (DOBV). At least three DOBV genotypes have been identified, in association with Apodemus flavicollis, A. agrarius and A. ponticus hosts, DOBV associated with A. flavicollis has been found to be more pathogenic with a fatality rate up to 12% [12][13][14]. According to Papa et al, 2016, DOBV is the only hantavirus detected in Albania and A. flavicollis was the only DOBV-positive rodent species [12,13,15].…”
Section: Discussionmentioning
confidence: 99%